2006
DOI: 10.1007/bf03168992
|View full text |Cite
|
Sign up to set email alerts
|

Co-immunotherapy with interleukin-2 and taurolidine for progressive metastatic melanoma

Abstract: Co-administration of taurolidine with high-dose rIL-2 in stage IV melanoma patients appears to greatly enhance the tolerability of this regime without diminishing its therapeutic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…However, the use of IL-2 is restricted by its dose-dependent toxicity, which is mainly VLS. Some studies have been done to diminish IL-2 toxicity and maintain its effectiveness, such as coimmunotherapy with IL-2 and other factors, like taurokidine, temozolomide, GM-CSF, and IFN-␣ (7,8). Nonetheless, at present, there is no specific therapy against VLS.…”
Section: Ascular Leak Syndrome (Vls)mentioning
confidence: 99%
“…However, the use of IL-2 is restricted by its dose-dependent toxicity, which is mainly VLS. Some studies have been done to diminish IL-2 toxicity and maintain its effectiveness, such as coimmunotherapy with IL-2 and other factors, like taurokidine, temozolomide, GM-CSF, and IFN-␣ (7,8). Nonetheless, at present, there is no specific therapy against VLS.…”
Section: Ascular Leak Syndrome (Vls)mentioning
confidence: 99%
“…Experimental studies have shown minimal toxicity or hematological adverse effects so far. The treatment of TRD has been shown to reduce tumor growth in various animal experiments [1,13,14] . Previous experimental data of our own demonstrated that intraperitoneal application of TRD in rats after establishment of an experimental tumor model did not result in any relevant side effects [7,15] .…”
Section: Discussionmentioning
confidence: 99%
“…At present, the standard therapy comprises surgical resection with a wide margin of healthy tissue, typically accompanied by radiation treatment in order to reduce the chance of local recurrence (4,5). Unfortunately, distant metastasis occurs in ~50% of all patients, and surgical treatment is thus unavailable (6,7).…”
Section: Introductionmentioning
confidence: 99%